How Well Does a Student-Run Free Clinic Care for Diabetic Patients? - Laitman, Benjamin M; Mosley, Grace; Thomas, David C; Meah, Yasmin S (Journal of Student-Run Clinics, 2017)
Background: Student-run free clinics are an integral safety net for the uninsured, particularly for managing chronic conditions such as diabetes. A previous study of diabetes care at the East Harlem Health Outreach Partnership (EHHOP) demonstrated that patients receive comparable care to insured patients. In this study we explore the clinic’s achievement and maintenance of glycemic targets in adult type II diabetes patients. Methods: This was a retrospective study examining hemoglobin A1c (A1c) values from 2009-2012. Patients with baseline A1c ≥7.0% and ≥2 A1c values recorded were included in this study. Data was analyzed at baseline, 6 months, 1 and 2 years from diagnosis, and at final recorded visit. Prescribed medications were also assessed. Results were compared with other published diabetes quality-of-care metrics. Results: Forty-four patients met entry criteria. Mean baseline A1c was 10.1%±2.3% and decreased to 8.3±2.3% by 6 months of treatment. By their final visit, 40.9% (n=18) of patients achieved an American Diabetes Association A1c goal of ≤7.0%. Of those patients with A1c values above target, 15 reduced their A1c to ≤8.0%. Patients whose A1c values reached ≤7.0% maintained stable low A1c levels for the remainder of follow-up. Over 90% of patients achieved targets with ≥1 hypoglycemic medication. Patients least able to achieve goal A1c were more likely to take a greater number of medications. These results are comparable to other published metrics. Conclusions: Despite resource limitations, uninsured patients at student-run free clinics are able to reach and maintain target A1c at comparable rates to their insured counterparts.